1997
DOI: 10.1021/om960752v
|View full text |Cite
|
Sign up to set email alerts
|

Carbenes as Pure Donor Ligands:  Theoretical Study of Beryllium−Carbene Complexes1

Abstract: Quantum chemical ab initio calculations at the MP2/6-31G(d) level of theory are reported for the beryllium−carbene complexes Be(CX2) n 2+ (X = H, F; n = 1−4), ClBe(CX2) n + (X = H, F; n = 1−3), and Cl2Be(CX2) n (X = H, F; n = 1, 2). The complex ClBe(C(NH2)2)3 + has also been calculated. Where feasible, the bond energies of some molecules are reported at MP4/6-311G(d)//MP2/6-31G(d). Analysis of the bonding situation with the help of the natural bond orbital method shows that the carbene ligands are pure dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 39 publications
(29 reference statements)
0
51
0
2
Order By: Relevance
“…The bond distances between carbene C atom bonded to Pd and N atoms in the NHC ring are shorter than the other C-N bond distances. This is possibly indicative of a greater partial double-bond character due to partial electron donation by N to the carbene C atom donor [24][25]. Theoretical study also indicates that the stability of these carbenes is due to electron donation from the nitrogen lone pairs into the formally empty p(p) orbital of the carbene C atom (herein C1 and C2) [26].…”
Section: Resultsmentioning
confidence: 99%
“…The bond distances between carbene C atom bonded to Pd and N atoms in the NHC ring are shorter than the other C-N bond distances. This is possibly indicative of a greater partial double-bond character due to partial electron donation by N to the carbene C atom donor [24][25]. Theoretical study also indicates that the stability of these carbenes is due to electron donation from the nitrogen lone pairs into the formally empty p(p) orbital of the carbene C atom (herein C1 and C2) [26].…”
Section: Resultsmentioning
confidence: 99%
“…[14][15][16] This tendency is amplified upon coordination to a metal centre. [17,18] Aromaticity within the heterocycle also contributes to the NǞC π-donation, so that upon coordination, unsaturated 2-imidazolylidenes are more stable than saturated 2-imidazolidinylidene counterparts. [19] Moreover, even though the difference in relative bond-dissociation energies between such saturated and unsaturated carbene complexes is rather small, their catalytic properties are quite different.…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with the values of the literatures [16,17]. The C1-N9 and N2-C9 bond distances are 1.322(6) and 1.351(6) Å, respectively, which are significantly shorter than the other C carbene −N bond distances present in the complexes, for instance the N1-C10 is 1.479(6) Å, and is possibility indicative of greater partial double bond character in these C carbene −N bonds due to partial electron donation by nitrogen to the carbene carbon donor [1,19]. The theoretical studies also indicated that the stability of these carbenes is due to electron donation from the nitrogen lone pairs into the formally vacant p(π) orbital of the carbene carbon [18].…”
Section: Comparison Ofmentioning
confidence: 82%